Wolves, Crows, and Spiders: An eclectic Literature Review inspires a Model explaining Humans’ similar Reactions to ecologically different Wildlife - Jürgens, Uta Maria; Hackett, Paul M. W. (Frontiers in Environmental Science, 2021)
Coming from the vantage point of managing human relations to potentially problematic wildlife, we bring the following questions: Where do people’s emotionally vigorous and polarized reactions originate? Why do these reactions to different scenarios of human-wildlife conflict appear similar? In this paper we provide the findings from an eclectic review of purposefully sampled literature on human relations to wolves, corvids and spiders. Based on this synthesis, we propose three answers to those questions: I. The emotional vigor inherent in human-wildlife conflicts is caused by the activation of deep-seated and emotionally loaded factors, specifically worldviews on human-nature relations more broadly, an integral human motivation for seeking control, and symbolic associations to darkness. II. The opposing attitudes on human-wildlife relations derive from people’s diverging worldviews and different degrees of wanting control in a situation of human-wildlife conflict. III. Despite ecological specificities, various cases of human-wildlife conflicts may evoke similar mental processes and, accordingly, the same reactions in people. Consequentially, it is possible to develop transferable solutions that may contribute to managing challenges in different instances of human-wildlife encounters.